2009
DOI: 10.2166/wst.2009.515
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing stage 1 and 2 reverse osmosis permeates using fluorescence spectroscopy

Abstract: Fluorescence excitation-emission matrix (EEM) spectroscopy was used to distinguish between two stages of reverse osmosis (RO) permeates as the first step towards investigating the potential application of fluorescence as a monitoring tool for membrane performance. The signal response of several fluorescence peaks present in Stage 1 and Stage 2 RO permeates of an advanced water treatment plant were compared. The humic-like fluorescence region was found to have the largest percentage difference between stages an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The bulk characteristics of DOC in RO permeate have been investigated using ion exchange (Fujita et al 1996;Drewes et al 2003), size exclusion chromatography with organic carbon and nitrogen detection (Henderson et al 2010) and fluorescence excitation emission spectroscopy (Singh et al 2009). These studies have shown that DOC in RO permeates do not normally contain organic material of molecular weight greater than 500 Da (Drewes et al 2003), and that, based on Amberlite XAD™ resin fractionation, up to 50% of DOC is hydrophilic (Fujita et al 1996).…”
Section: Drinking Water Augmentation Is Still Considered a High-risk mentioning
confidence: 99%
“…The bulk characteristics of DOC in RO permeate have been investigated using ion exchange (Fujita et al 1996;Drewes et al 2003), size exclusion chromatography with organic carbon and nitrogen detection (Henderson et al 2010) and fluorescence excitation emission spectroscopy (Singh et al 2009). These studies have shown that DOC in RO permeates do not normally contain organic material of molecular weight greater than 500 Da (Drewes et al 2003), and that, based on Amberlite XAD™ resin fractionation, up to 50% of DOC is hydrophilic (Fujita et al 1996).…”
Section: Drinking Water Augmentation Is Still Considered a High-risk mentioning
confidence: 99%
“…Very little research has been reported on applications of fluorescence spectroscopy for monitoring RO membrane performance. However, preliminary investigations have suggested that the technique may be sufficiently sensitive to detect small variations in RO permeate qualities [33].…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary investigations found the technique sufficiently sensitive to detect subtle changes in permeate quality pertaining to differences in direct feed quality within multiple staged RO systems. 23 Parallel factor analysis (PARAFAC) of treatment processes at several advanced recycled water treatment plants (including RO) demonstrated that five common fluorescence components were present in four or more plants in that study and that the information derived from monitoring these components would be equivalent to monitoring full EEMs. 24 The fluorescent component G3 (λ Ex/Em = 350/428 nm) which was described as a wastewater/nutrient enrichment tracer from that study, matched closely with the fluorescent regions commonly described as 'Peak C' (λ Ex/Em = 320-350/410-430 nm).…”
Section: Introductionmentioning
confidence: 85%